Proton-driven coordination-induced spin state switch (PD-CISSS) of iron(ii) complexes. Issue 5 (3rd January 2017) - Nowak, René; Prasetyanto, Eko Adi; De Cola, Luisa; Bojer, Beate; Siegel, Renée; Senker, Jürgen; Rössler, Ernst; Weber, Birgit
Abstract : A pH dependent reversible spin state switch is observed for strong field iron(ii ) complexes in line with a significant relaxivity gap between the high spin and the low spin state. Abstract : Here we report the completely reversible spin state switch of the naturally diamagnetic tris(bipyridine)iron(ii ) complex and the spin crossover complex bis(2, 6-bis(1 H -pyrazol-3-yl)pyridine)iron(ii ) by the variation of the pH followed by 1 H-NMR, UV-Vis spectroscopy, and magnetic and relaxivity measurements in solution and as composite materials encapsulated in a zeolite matrix.